CD45 exclusion and crosslinking-based receptor signaling together broaden FcεRI reactivity - Felce, J; Sezgin, E; Wane, M; Brouwer, H; Dustin, M; Eggeling, C; Davis, S (American Association for the Advancement of Science, 2018)
For many years, the high-affinity receptor for immunoglobulin E (IgE) FcεRI, which is expressed by mast cells and basophils, has been widely held to be the exemplar of cross linking (that is, aggregation-dependent) signaling receptors. We found, however, that FcεRI signaling could occur in the presence or absence of receptor crosslinking. Using both cell and cell-free systems, we showed that FcεRI signaling was stimulated by surface-associated monovalent ligands through the passive, size-dependent exclusion of the receptor-type tyrosine phosphatase CD45 from plasma membrane regions of FcεRI-ligand engagement. Similarly to the T cell receptor, FcεRI signaling could also be initiated in a ligand-independent manner. These data suggest that a simple mechanism of CD45 exclusion–based receptor triggering could function together with crosslinking-based FcεRI signaling, broadening mast cell and basophil reactivity by enabling these cells to respond to both multivalent and surface-presented monovalent antigens. These findings also strengthen the case that a size-dependent, phosphatase exclusion– based receptor triggering mechanism might serve generally to facilitate signaling by noncatalytic immune receptors.